2014
DOI: 10.1016/j.psyneuen.2014.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Women's hormone levels modulate the motivational salience of facial attractiveness and sexual dimorphism

Abstract: 2Women's hormone levels modulate the motivational salience of facial attractiveness and sexual dimorphism AbstractThe physical attractiveness of faces is positively correlated with both behavioral and neural measures of their motivational salience. Although previous work suggests that hormone levels modulate women's perceptions of others' facial attractiveness, studies have not yet investigated whether hormone levels also modulate the motivational salience of facial characteristics. To address this issue, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…This finding contrasts with two studies that found elevated levels of estradiol at the peri-ovulatory phase were positively associated with women's preferences for facial masculinity (Ditzen et al, 2017;Roney et al, 2011), but supports another that reported no associations between salivary hormone levels and women's preferences for masculinity (Jones et al, 2017). Behavioral studies quantifying women's motivation to attend to facial stimuli using key tests found that ratios of estradiol relative to progesterone were positively associated with women's attention toward feminised and attractive female faces and masculinised, but not necessarily attractive, male faces (Wang et al, 2014). However, other studies that also used within-subject designs found positive associations between changes in testosterone but not estradiol or progesterone and preferences for facial masculinity (Bobst et al, 2014;Welling et al, 2007).…”
Section: Discussionsupporting
confidence: 60%
“…This finding contrasts with two studies that found elevated levels of estradiol at the peri-ovulatory phase were positively associated with women's preferences for facial masculinity (Ditzen et al, 2017;Roney et al, 2011), but supports another that reported no associations between salivary hormone levels and women's preferences for masculinity (Jones et al, 2017). Behavioral studies quantifying women's motivation to attend to facial stimuli using key tests found that ratios of estradiol relative to progesterone were positively associated with women's attention toward feminised and attractive female faces and masculinised, but not necessarily attractive, male faces (Wang et al, 2014). However, other studies that also used within-subject designs found positive associations between changes in testosterone but not estradiol or progesterone and preferences for facial masculinity (Bobst et al, 2014;Welling et al, 2007).…”
Section: Discussionsupporting
confidence: 60%
“…Data on 45 of these women's voice preferences are reported in Pisanski et al (2014). Data on the reward value of adult facial attractiveness and infant facial cuteness for 39 and 45 of these women are reported in Wang et al (2014) and Hahn et al (2015), respectively. Data on the facial coloration of 64 of these women are reported in Jones et al (2015).…”
Section: Participantsmentioning
confidence: 99%
“…Our analyses considered the possible effects of testosterone, estradiol, progesterone, estradiolto-progesterone ratio, and cortisol, as well as women's partnership status. This type of design has recently been used to investigate the hormonal correlates of changes in women's responses to facial and vocal cues Pisanki et al, 2014;Wang et al, 2014) and appearance .…”
Section: Introductionmentioning
confidence: 99%
“…These images were then aligned on pupil position and masked so that clothing was not visible. These images have been used in other recent face perception studies Wang, Hahn, Fisher, DeBruine, & Jones, 2014).…”
Section: Stimuli For Health Preference Testmentioning
confidence: 99%